Online Appendix to “Energy Efficiency and Fluctuations in CO2 Emissions” - Jo, Soojin; Karnizova, Lilia (Université d'Ottawa | University of Ottawa, 2021)
This appendix provides additional information and analyses for “Energy Efficiency and Fluctuations in CO2 Emissions.” Section 1 explains data sources and transformations. Section 2 covers a variety of robustness checks conducted for our baseline VAR results. Section 3 reports the results related to the analysis of emissions and energy consumption of major energy-use sectors. Specifically, section 3.1 demonstrates the impact of VAR estimation and model uncertainty on the inference from distributed lag models (DLMs). Section 3.2 reports the responses of energy consumption by sector to a negative correlation (NC) shock. Section 4 lays out a full description of the multi-sector dynamic stochastic general equilibrium model with pollution (E-DSGE model), which is used in our main text. Finally, section 5 includes additional results on the implications of weather extremes for our interpretation of NC shocks as changes in the energy efficiency of consumer products.
Keywords: 2108E; CO2 emissions; energy efficiency; E-DSGE; sign restrictions